Dietary differences have contrasting effects on the seed dispersal potential of the titi monkey Callicebus coimbrai in north-eastern Brazil. (March 2015) - Baião, Sirley A.A.; Correia, Fernanda B.A.; Ferrari, Stephen F.
Abstract: Gut transit times and dispersal distances of seeds ingested by Callicebus coimbrai at two localities were estimated by tracing seeds found in faeces to feeding sites. Feeding events and faecal samples were recorded/collected and mapped by GPS between April and July, 2012. Junco group fed almost exclusively on fruit, whereas Trapsa group fed on fruit and leaves/flowers in similar proportions. A much higher proportion of faecal samples from Junco contained seeds (47.9%, n = 244, vs. 33.6%, n = 177), and contained more seeds, on average (3.0 ± 2.8 vs. 2.1 ± 2.1) than those from Trapsa. However, gut transit times were absolutely longer at Trapsa (mean = 4.87 ± 1.48 h, n = 6, vs. 2.85 ± 0.53 h, n = 13 daytime events), and dispersal distances were significantly longer (200 ± 81.0 m vs. 126 ± 53.4 m). The evidence indicates that, while the more folivorous diet at Trapsa was reflected in a much lower faecal seed count, it was also associated with longer gut transit times, and significantly longer dispersal distances, i.e. while dispersing approximately half the seeds dispersed by Junco group, Trapsa group dispersed these seeds over almost twice the distance.